DECISION SUPPORT SYSTEM FOR ASSESSING SCHOLARSHIP RECIPIENTS USING THE TOPSIS METHOD AT SMPN 1 PULAU PANGGUNG - Prayuda, Aqsha; Lestari, Kanti; Ipnuwati, Sri (JECE (Journal of Ethics and Character Education), 2024)
The institution is constantly pushing its pupils to do better. Scholarships are a great incentive for students to strive for excellence. Grants are financial awards given to students based on their academic performance or demonstrated financial need, and are therefore not limited to those who are merely pursuing further education. Scholarships are available to pupils each year at Pulau Pangkalan 1 Middle School. Currently, these institutions rely on human judgment to choose which students merit scholarship money. There are still issues with the decision-making procedure for determining who is eligible for scholarships at SMP N 1 Pulau Panggung. All stakeholders must be happy with the outcome, and the decision-making process can involve competing priorities. The TOPSIS algorithm is a type of decision-support algorithm predicated on the notion that the optimal choice minimizes both the positive and negative distances to the optimal solution. An important goal of this study is to determine whether or not a decision support system can facilitate the picking of scholarship winners at SMP N 1 Pulau Panggung. The TOPSIS method was used to decide scholarship awards at SMP N 1 Pulau Panggung, and the results showed that alternative C, with a value of 0.819, was the best choice overall. At SMP N 1 Pulau Panggung, the decision support system is able to help with scholarship approval, it is claimed.